2009
DOI: 10.2165/00003495-200969100-00007
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole

Abstract: Rabeprazole (Aciphex, Alfence, Pariet) is a proton pump inhibitor (PPI) used for the treatment of adults with conditions requiring a reduction of gastric acid secretion such as erosive or ulcerative gastro-oesophageal reflux disease (GORD), non-erosive reflux disease (NERD), duodenal and gastric ulcers, and pathological hypersecretory conditions including Zollinger-Ellison syndrome (ZES). It is also used as part of combination therapy for the eradication of Helicobacter pylori, a pathogen frequently implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 81 publications
0
13
0
1
Order By: Relevance
“…Both H 2 blockers and PPIs can control acid hypersecretion in all patients who can take oral medications and are cooperative [2,8,32,57,172,173]. The preferred drugs are now PPIs, because of their long duration of action [8,32,57,172,174,175,176,177,178]. H 2 blockers to be effective are usually required at higher doses than used in conventional peptic disease (frequently up to 10 times the usual dose) and 4-6 h dosing is frequent [2,3,57,75].…”
Section: Medical Treatment Of Functional P-nets [125813141557mentioning
confidence: 99%
See 1 more Smart Citation
“…Both H 2 blockers and PPIs can control acid hypersecretion in all patients who can take oral medications and are cooperative [2,8,32,57,172,173]. The preferred drugs are now PPIs, because of their long duration of action [8,32,57,172,174,175,176,177,178]. H 2 blockers to be effective are usually required at higher doses than used in conventional peptic disease (frequently up to 10 times the usual dose) and 4-6 h dosing is frequent [2,3,57,75].…”
Section: Medical Treatment Of Functional P-nets [125813141557mentioning
confidence: 99%
“…PPIs are the drugs of choice because of their long duration of action allowing once or twice a day dosing in most patients. Studies show all available PPIs (omeprazole, lansoprazole, pantoprazole, rabeprezole, esomeprazole) are effective [8,32,57,172,174,175,176,177,178]. The recommended starting dose is equivalent to omeprazole 60 mg once per day in sporadic ZES and 40-60 mg b.i.d.…”
Section: Medical Treatment Of Functional P-nets [125813141557mentioning
confidence: 99%
“…While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80]. Nonetheless, other studies suggest CYP2C19 is important for all PPIs.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Rabeprazole is less susceptible to the influence of genetic polymorphisms for CYP2C19. Thus, it has greater and faster acid suppression compared to older PPIs [25]. Amoxicillin is one of the effective antibiotics to H. pylori with few side effects.…”
Section: Introductionmentioning
confidence: 99%